DEVELOPMENT OF SILICA-ALUIMA ACTIVE MATRIX WITH THE ADDITION OF PHOSPHOR AND POLYETHILENE GLYCOL (PEG) AS CRACKING CATALYST COMPONENT - Puspitasari, Ernawati
The active matrix is the initial cracking medium that serves to improve the performance of the catalyst. Widikrama and Kurniawan (2019) and Chen et al., (2004) added Phosphorus compounds to improve the physical properties and performance of the Silica-Alumina matrix. Another update was carried out by Ishihara et al., (2014) by adding PEG compounds as organic templates. The results of these experiments proved to be able to improve the physical properties and performance of the active matrix. Silica-Alumina matrix was synthesized using the sol method for the matrix with and without the addition of Phosphorus, and the sol-gel method for the matrix with the addition of PEG. The diffractogram of XRD analysis of the matrix with and without the addition of Phosphorus showed that the synthesized matrix had amorphous properties, while the matrix with the addition of PEG compounds identified the presence of Halite minerals, namely NaCl. Matrix characterization using BJH showed type IV hysteresis, which indicated the presence of mesopore in all of the synthesized active matrix. The performance of the active matrix in the form of activity and conversion descreased, but was compensated by an increase in the yield of mid-distillate, namely LCO. The level of deactivation and stability of the active matrix was moderate, due to coke formation in the range of 9,073-10,808%. The addition of 1% Phosporus compound is considered more effective than the addition of 10% and 20% PEG and the increase in Silica composition, because it can increase the size of pore diameter with a slight decrease in the surface area of the active matrix. As well as a slight decrease in catalytic activity and reaction conversion to increase the LCO recovery.